Effective online lectures| Improving practice through design and pedagogy - Bese, Terry Lane (Pepperdine University, 2016)
The purpose of this research project was to improve the practice of using online lectures at a small private university. Using action research methodology, the researcher worked with a group of five university instructors to refine the use of online lectures through design and pedagogical practice. Beginning with a template or guide based on the literature, the instructors developed online lectures connected with a student activity. Following the principles of the TPACK framework, instructors were urged to develop student activities that worked best for their specific content as well as their desired student outcomes. Two cycles of implementation, analysis, and modification were used to refine the template and the student activities. Data were gathered from the students who viewed the online lectures and from the faculty through focus group meetings after each cycle. Analysis of both the students’ experience and the instructors’ experience led to minor changes in the template but more significant changes to the associated student activities. Findings suggest that the effective use of online lectures depends largely on the student activity included with the lecture; in other words, pedagogy is at least as important as design. Other factors, such as practice and experience with developing online lectures are needed to develop the instructors’ expertise with both technical issues as well as pedagogical issues. Although the online lecture template and suggested activities list were honed to a degree of effectiveness, it will take an ongoing process of analysis and modification to keep this tool relevant in the coming years.